The Social Impact of Living with Developmental Coordination Disorder as a 13-year-old. (August 2013) - Payne, Sally; Ward, Gillian; Turner, Andrew; Taylor, M Clare; Bark, Chris
Introduction: Children with developmental coordination disorder are frequently referred to an occupational therapist. However, while there is a growing body of research about developmental coordination disorder, there is a paucity of research from the perspective of adolescents living with the condition. Purpose: The purpose of this study was to investigate the experience of teenagers living with developmental coordination disorder from their own perspective. This article presents findings from interviews with teenagers aged 13 years. Method: The research adopted an interpretive phenomenological approach. Semi-structured interviews were carried out to examine the personal experiences of six individuals diagnosed with developmental coordination disorder. Interviews were audio-recorded, transcribed and analysed using in-depth ideographic, inductive and interrogative techniques. Findings: All participants felt that the visible and hidden effects of their condition had an impact on their relationships with peers and family members. Three sub-themes emerged: (1) relationships with peers; (2) relationships with parents and (3) relationships with siblings. Conclusion: Participants described how their personal attributes, shared interests and the attitudes of others affected their relationships and social participation at home, at school and in the community. Understanding the issues that matter to teenagers with developmental coordination disorder will help occupational therapists to offer advice and meaningful interventions that increase teenagers' social confidence and participation.